MRNA Transcription, Translation, and Defects in Developmental Cognitive and Behavioral Disorders - Smith, Moyra (Frontiers in Molecular Biosciences, 2020)
Growth of expertise in molecular techniques, their application to clinical evaluations and the establishment of data bases with molecular genetic information has led to greater insights into the roles of molecular defects in impaired neuronal development and impaired cognitive and behavioral functions. The goal of this review is to examine new insights into underlying processes in gene expression, including transcription, translation and cellular protein synthesis and the relevance of genetic alterations in these processes in cognitive and behavioral disorders and epilepsy.